Building a new safety net for sick workers - Junghyun Kwo (Korea Development Institute (KDI), 2022)
The effective rollout of the Sickness Benefits as a social safety net for sick workers hinges on sick leave readily accessible in the workplace. To that end, sickness benefits should include assistance for firms vulnerable to extra costs incurred by sick leave. Also, the level of sickness benefits should be differentiated based on the duration and severity of illness or injury. To ensure the sustainability of Sickness Benefits, the scheme further requires measures to strengthen medical certification and to support workers' return to work after a spell of sick leave.
Keywords: 330